Incidence of Hyperbilirubinemia and Urinary Tract Infection (UTI) in Asymptomatic Term Neonates Under Two Weeks of Age - Marjaneh Zarkesh; Afshin Safayi Assl; Sara Ramtinfar; Maryam Shakiba (Mashhad University of Medical Sciences, 2015)
Background: Hyperbilirubinemia is a common cause of referral to neonatal care units. According to several studies, jaundice is among the primary symptoms of urinary tract infection (UTI) in neonates. This study aimed to determine the prevalence of UTI in asymptomatic term neonates diagnosed with indirect hyperbilirubinemia within the first two weeks of birth. Methods: This prospective study was conducted on 314 term neonates under 14 days of age, presented with unexplained indirect hyperbilirubinemia for UTI (total bilirubin level: 15 mg/dl). Subjects were referred to 17-Shahrivar Children's Hospital in Rasht during 16 months, and neonates diagnosed with UTI were further investigated. Results: Out of 314 neonates, 12 patients (3.8%) were diagnosed with UTI, and E. coli was the most prevalent pathogen in these patients. No significant differences were observed between neonates with and without UTI in terms of gender, birth weight, age, bilirubin level on admission and mode of delivery (P>0.05). Additionally, pyuria and bacteriuria were significantly more prevalent among UTI patients compared to other neonates (P